2016
DOI: 10.1371/journal.pone.0158602
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization and Genetic Dissection of Growth Period Traits in Soybean (Glycine max) Using Association Mapping

Abstract: The growth period traits are important traits that affect soybean yield. The insights into the genetic basis of growth period traits can provide theoretical basis for cultivated area division, rational distribution, and molecular breeding for soybean varieties. In this study, genome-wide association analysis (GWAS) was exploited to detect the quantitative trait loci (QTL) for number of days to flowering (ETF), number of days from flowering to maturity (FTM), and number of days to maturity (ETM) using 4032 sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
4
9
0
Order By: Relevance
“…In this study, a relatively complex population structure (K = 7) was revealed in comparison of previous reports in which population structures (K = 2, 4, 9) were disclosed (Sonah et al, 2015 ; Liu Z. X. et al, 2016 ; Fang et al, 2017 ). After eliminating batch specific or biased markers, the set of 4471 markers might represents the core markers for this set of germplasm (Data Sheet 1 , ftp://159.226.208.134/public/SNP_data.zip ).…”
Section: Resultssupporting
confidence: 51%
“…In this study, a relatively complex population structure (K = 7) was revealed in comparison of previous reports in which population structures (K = 2, 4, 9) were disclosed (Sonah et al, 2015 ; Liu Z. X. et al, 2016 ; Fang et al, 2017 ). After eliminating batch specific or biased markers, the set of 4471 markers might represents the core markers for this set of germplasm (Data Sheet 1 , ftp://159.226.208.134/public/SNP_data.zip ).…”
Section: Resultssupporting
confidence: 51%
“…For a better comparison, the correlations among the three traits were calculated for each MG within each MEV, but the results have to be treated with caution because the analysis was based on only 15 genotypes. The reason for the moderately positive correlations between flowering and maturity observed here and also by Jia et al (2014), as compared to the high correlations reported by Alliprandini et al (2009) andLiu et al (2016), is mainly due to the low variation within each MG. Especially flowering is less variable among very early material because of its photoperiod insensitivity, which was also observed by Zhai et al (2014).…”
Section: Duration Of Developmental Phases and Implications For Yield supporting
confidence: 46%
“…() and Liu et al . (), is mainly due to the low variation within each MG. Especially flowering is less variable among very early material because of its photoperiod insensitivity, which was also observed by Zhai et al .…”
Section: Discussionmentioning
confidence: 99%
“…This nding further con rmed that co-mapping of QTLs caused by single gene pleiotropy. The co-mapping of QTLs can help breeders identifying favorable alleles for multiple traits simultaneously in marker-assisted breeding [39].…”
Section: Snp Markers With Pleiotropic Effectsmentioning
confidence: 99%